2011
DOI: 10.2217/rme.11.100
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Tissue Outcome of Ovine and Human Engineered Heart Valve Constructs: Relevance for Tissue Engineering

Abstract: The results suggest that the culture process of ovine tissues can be controlled, whereas the mechanical properties, and hence functionality, of tissues originating from human material are more difficult to control. On-line evaluation of tissue properties during culture or more early cellular markers to predict the properties of autologous tissues cultured for individual patients are, therefore, of utmost importance for future clinical application of autologous heart valve tissue engineering. As an example, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A number of synthetic (poly-glycolic acid, polylactic acid, poly-4-hydroxybutyrate, polyhydroxyalkanoate) (Sodian, Hoerstrup et al 2000; Sutherland, Perry et al 2005; Balguid, Mol et al 2009; Gottlieb, Kunal et al 2010; Ramaswamy, Gottlieb et al 2010; Sales, Mettler et al 2010; Schmidt, Dijkman et al 2010; Sodian, Schaefermeier et al 2010; Eckert, Mikulis et al 2011; van Geemen, Driessen-Mol et al 2012) and biological polymeric (collagen I, fibrin) (Neidert and Tranquillo 2006; Robinson, Johnson et al 2007; Flanagan, Sachweh et al 2009) scaffolds have been created, mechanically conditioned in vitro , and tested in animal models. In the longest such trial to date (8 months within a growing sheep model), engineered valves (leaflet + conduit) were still functional but mildly stenotic, suggesting that the leaflets lacked sufficient compliance (Sutherland, Perry et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A number of synthetic (poly-glycolic acid, polylactic acid, poly-4-hydroxybutyrate, polyhydroxyalkanoate) (Sodian, Hoerstrup et al 2000; Sutherland, Perry et al 2005; Balguid, Mol et al 2009; Gottlieb, Kunal et al 2010; Ramaswamy, Gottlieb et al 2010; Sales, Mettler et al 2010; Schmidt, Dijkman et al 2010; Sodian, Schaefermeier et al 2010; Eckert, Mikulis et al 2011; van Geemen, Driessen-Mol et al 2012) and biological polymeric (collagen I, fibrin) (Neidert and Tranquillo 2006; Robinson, Johnson et al 2007; Flanagan, Sachweh et al 2009) scaffolds have been created, mechanically conditioned in vitro , and tested in animal models. In the longest such trial to date (8 months within a growing sheep model), engineered valves (leaflet + conduit) were still functional but mildly stenotic, suggesting that the leaflets lacked sufficient compliance (Sutherland, Perry et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies seem promising and the use of human AFCs in vitro or in immunodeficient rodent models represents an important step, more extensive in vivo experiments using autologous AFCs in immunocompetent experimental models seem mandatory before a first human clinical application. In addition, when dealing with tissue‐engineered constructs the assessment of the ex vivo engineered constructs in biomechanical environments comparable to the human physiology seems obligatory (van Geemen et al ., ). Therefore, several groups have started isolating and characterizing autologous amniotic fluid‐derived cells from different large animal models, including porcine (Chen et al ., ) or equine (Park et al ., ) materno‐fetal models.…”
Section: Discussionmentioning
confidence: 97%
“…This seems crucial in order to assess the adequate in vivo functionality of implanted constructs and cells, but also in order to exclude potential adverse effects. While extensive preclinical research in non‐human primates has raised ethical concerns, the ovine model represents one of the most accepted and broadly used preclinical in vivo models for therapeutic approaches (van Geemen et al ., ). Among others, it has been established as a standard model for preclinical evaluation of haematopoietic stem cell transplantations (Porada et al ., ), orthopaedic implants (Schneider et al ., ), therapeutic cloning (Berardino, ), fertility treatment (Byun et al ., ), prenatal therapeutic interventions (Lapa Pedreira et al ., ), fetal stem cell injections (Schoeberlein et al ., , Emmert et al ., ), as well as any cardiovascular device in vivo assessment due to its advanced calcification and degeneration properties (Barnhart et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Although this has been demonstrated in long‐term animal studies [2], studies in humans have yet to be performed to evaluate the efficacy of this approach. Recent studies by our group have demonstrated differences in cardiovascular tissues engineered from human and ovine cells [3]. This further indicates the relevance of specific, deviating culture protocols for either ovine or human engineered tissues and emphasizes that results obtained with either species cannot be easily compared.…”
Section: Introductionmentioning
confidence: 96%